Exploring breastfeeding intentions and behaviors from a socio-ecological perspective - Anglamega Seidu, Rose Madodzi (My University, 2026)
The health benefits of breastfeeding for infants, including cognitive development, health, and child survival, are well-documented globally. Key organizations like the World Health Organization (WHO), the American Academy of Pediatrics, and the U.S. Surgeon General recommend breastfeeding for the first six months of life due to the significant health advantages for both the infant and the mother. Despite these recommendations, breastfeeding rates remain suboptimal in the U.S. This research aims to explore three key areas related to breastfeeding. First, an ecological study analyzed the relationship between statewide breastfeeding rates and statewide breastfeeding support indicators using data from the CDC's 2019 Breastfeeding Report Card (Chapter 2). The study found that early introduction of formula before 2 days was negatively associated with all breastfeeding durations at 12 months ([beta] = -.59, p < .12), exclusively breastfeeding at 3 ([beta] = -.1.06, p < .001) and exclusively breastfeeding at 6 months ([beta] = -.59, p < .001) respectively, while state-level breastfeeding support, measured by the Hospital Maternity Practices in Infant Nutrition and Care (mPINC) indicator, was positively correlated with longer breastfeeding durations at 6 months ([beta] = .71, p < .01), at 12 months ([beta] = .61, p < .01), exclusively breastfeeding at 3 ([beta] = .52, p < .01), and exclusively breastfeeding at 6 months ([beta] = .37, p < .01). Secondly, individual demographic and infant feeding data from the CDC’s 2019 National Immunization Survey (n = 29,217) were analyzed to explore the relationship between early formula introduction and early cessation of breastfeeding (Chapter 3). Results showed that 72.7% of breastfed infants were still breastfeeding at 6 months. Early formula introduction, either before 2 days or before 30 days, significantly reduced the likelihood of breastfeeding continuation. Key predictors for early formula introduction included maternal age ≥ 29 years and first-born status of the infant. Lastly, a cross-sectional web-based survey of expectant mothers (n = 222) across the U.S. was conducted to assess their breastfeeding attitudes and intentions. The survey aimed to understand if exposure to information about the infant formula shortage affected their breastfeeding attitudes (Chapter 4). The study used validated instruments, including the Iowa Infant Feeding Attitude Scale (IIFAS) and the Infant Feeding Intention (IFI) scale, as well as a novel self-developed tool measuring the frequency of exposure to information about formula shortage (i.e., the Formula Shortage Exposure Scale). The mean score on the Infant Feeding Attitude scale was M = 54.89, SD = 7.99, with scores ranging from 34 to 75. The mean score on the Infant Feeding Intentions scale was M = 11.90, SD = 3.93, with a range of 0 to 16. The mean Formula Shortage Exposure Scale score was M = 28.73, SD = 7.77, with scores ranging from 11 to 44. Infant feeding attitude scores were positively associated with feeding intention scores (B = 1.37, p < .001). However, formula shortage exposure scores were not significantly associated with either feeding intention (B = –0.09, p = 0.820) or feeding attitudes (B = –0.15, p = .129). Significant differences in formula shortage exposure scores were found based on age, F(1, 219) = 15.43, p < .001; education level, F(2, 218) = 6.65, p < .001; WIC participation, F(1, 220) = 16.87, p < .001; and monthly income, F(2, 216) = 11.82, p < .001. These demographic factors, however, were not significantly associated with Infant Feeding Intentions scores. In summary, these combined studies highlight the multifactorial determinants of breastfeeding, emphasizing the complex interplay of physiological, behavioral, and socioeconomic factors that influence breastfeeding outcomes. This research highlights the critical role of breastfeeding support in prolonging breastfeeding duration and the negative impact of early formula introduction. The findings regarding early introduction of formula are particularly noteworthy given that the proportion of breastfed infants supplemented with formula before 2 days of age rose from 15.5% in 2014 to 20.5% in 2021. Future research is needed to assess the impact of specific interventions intended to increase breastfeeding initiation and duration.
Keywords: Breastfeeding; Child nutrition; Infant formula; Infant formula shortage; Breastfeeding intentions; Breastfeeding attitudes; Hospital maternity practices in Infant nutrition and care; Human milk; Maternity care; Public health surveillances; Breastfeeding outcomes; Early formula feeding